Mood fluctuation in Antarctic expeditioners: does one size fit all?. (28th March 2019) - Hawkes, Clare; Norris, Kimberley; Ayton, Jeff; Paton, Douglas
Abstract: It has long been argued that mood fluctuation patterns in Antarctic expeditioners are largely homogeneous. This research investigated mood fluctuation patterns throughout all the stages of Antarctic deployment using latent class growth analysis. Utilising advanced statistical methods, such as latent class growth analysis, can greatly help in identifying if mood fluctuation patterns experienced by Antarctic expeditioners are homogenous, and provide insight into mood fluctuation patterns, which was not possible with traditional group-based quantitative methods. Gaining a greater insight into mood fluctuation patterns in Antarctic expeditioners can assist with the development, and implementation of, strategies to assist with expeditioner well-being. The analysis was conducted on 423 expeditioner from the Australian Antarctic program between the 2005-2009 Antarctic deployment seasons. The results supported the notion that mood fluctuation patterns in expeditioners within the Australian-Antarctic programme were largely homogeneous, as a 1-class cubic latent class growth model was identified as being the optimal fit for the dataset. Theoretical and practical implications are discussed in relation to research and prevention and intervention strategies.